Lifespan extension and elevated hsp gene expression in Drosophila caused by histone deacetylase inhibitors. - Zhao, Y.; Sun, H.; Lu, J.; Li, X.; Chen, X.; Tao, D.; Huang, W.; Huang, B. (Journal of Experimental Biology, 2005)
The heat shock proteins (Hsps) play a positive role in lifespan determination, and histone acetylation has been shown to be involved in transcription of hsp genes in Drosophila. To further determine if hsp22 and hsp70 expression is correlated with lifespan, and if histone acetylation participates in this process, RNA levels for hsp22 and hsp70 were analyzed throughout the lifespan in the long-lived and short-lived iso-female lines. The results showed that hsp22 and hsp70 RNA levels were higher in long-lived line than in short-lived line and that the long-lived flies responded more rapidly to heat but were more tolerant to high temperature. Moreover, we investigated the influences of histone acetylation modification on longevity and on hsp gene expression by using histone deacetylase (HDAC) inhibitors TSA and BuA. The results demonstrated that both inhibitors were able to extend the lifespan and promote hsp22 and hsp70 expression. However, the optimal concentrations of these inhibitors, and probably the mechanisms of their actions, vary with the genetic background. In addition, we showed that HDAC inhibitors caused the hyperacetylation of core histone H3, implicating the involvement of chromatin modulation in hsp gene transcription. These data suggested a close correlation among histone acetylation, hsp gene expression and longevity in D. melanogaster.